Advanced Tree Risk Assessment: Resistance Recording Drills - Drew McLean; Andrew Koeser; Gitta Hasing (EDIS, 2014)
Resistance recording drills are specialized pieces of decay detection equipment that may be used as part of an advanced risk assessment. While not required for tree risk assessment work, resistance recording drills have been shown to be effective in helping arborists detect and document internal tree decay in trees. This 5-page fact sheet was written by Drew McLean, Andrew Koeser, and Gitta Hasing, and published by the UF Department of Environmental Horticulture, October 2014.